(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study investigates customer perspectives towards online bus ticketing in Thoothukudi, focusing on user experiences, satisfaction levels, and the factors influencing their preferences. Utilizing a mixed-methods approach, data were collected through surveys and interviews with a diverse group of bus ticketing users. The findings reveal that convenience, user interface, payment options, and customer service significantly impact user satisfaction. While most respondents appreciate the ease of online booking, challenges such as technical issues and limited payment methods were noted. The study concludes with recommendations for improving online bus ticketing services to enhance user experience and satisfaction.